Characterization of fruits of varieties of mango (Mangifera indica) conserved in Peru - Tuisima Coral, Lady Laura (2021)
The department of Piura is the main mango producer in Peru accounting for 66.7% of the national crop. The objective of the study was to characterize the fruits of forty varieties of mango preserved since 1969 in northwestern Peru. The fruits were harvested at the El Chira Agrarian Experimental Station, Department of Piura from December 2019 to January 2020. Thirteen quantitative fruit variables were evaluated: width, thickness, length, weight, seed width, seed thickness, seed length, percentage of seed, percentage of fresh skin, percentage of pulp, texture, °Brix, and pulp / seed ratios. The varieties with the highest percentage of pulp were Tommy Atkins, Haden x carabao 1, Irwin, and Jaffra, the latter was also the variety with the highest pulp / seed ratio (17.0). The varieties with the highest ° Brix were Blacman (21.3 ° Brix) and Julie (22.0 ° Brix). Knowledge of the fruit characteristics is essential for proper selection and use by the industry, especially those with a higher pulp weight to obtaining higher yields in processing.